SAT0573 Spatial Association of Subchondral Osteosclerosis and Immune Cell Infiltration in Osteoarthritis. (10th June 2014) - Geurts, J.; Pippenger, B.; Hirschmann, M.T.; Müller-Gerbl, M.; Valderrabano, V.; Hügle, T.
Abstract : Background: Subchondral bone sclerosis is a well known and potentially reversible feature of knee osteoarthritis (OA). The infiltration of immune cells into the subchondral bone in OA has been demonstrated previously. However, the exact assocation between immune cell infiltration and osteosclerosis, as well as their functional connection, remain elusive. Objectives: To investigate whether the interaction between bone and immune systems might be involved in the regulation of subchondral osteosclerosis in human OA. Methods: Computed tomography osteoabsorptiometry (CT-OAM) mapping of subchondral bone mineralization density (BMD) distribution was used to guide tissue preparation from nonsclerotic and sclerotic areas of explanted OA tibial plateaus. Cartilage degeneration and subchondral bone area fraction (B.Ar./T.Ar.) were evaluated using histomorphometric analyses. Presence of lymphocytes, macrophages and osteoclasts in subchondral bone marrow tissue was investigated using (immuno)histological and flow cytometry analyses for expression of CD3, CD20, CD68 and tartrateresistant acid phosphatase (TRAP). Alkaline phosphatase (ALP) activity was assessed in primary OA osteoblasts stimulated with conditioned medium from nonsclerotic and sclerotic subchondral bone. Results: Subchondral BMD distribution was heterogeneous and displayed focal areas of high density that macroscopically showed severe cartilage degeneration. Histomorphometry demonstrated a strong positive correlation between Mankin score and subchondral B.Ar/T.Ar. Immunohistological and flow cytometry analyses of subchondral bone marrow tissue showed a highly specific increase in CD68pos macrophages and multinucleated cells and CD20pos B-lymphocytes in sclerotic compared with nonsclerotic subchondral bone. Correspondingly, increased numbers of functional TRAPpos osteoclasts associating with CD34pos vascular structures were detected. Sclerotic OA osteoblasts showed increased basal alkaline (ALP) phosphate activity. Conditioned medium from sclerotic bone pieces, unlike nonsclerotic bone pieces, failed to induce osteoblastic ALP activity. Conclusions: Enhanced marrow immune cell infiltration and osteoclast activity, along with phenotypic alterations in osteoblasts are involved in uncoupled and aberrant bone remodeling. This indicates that immune cells induce a 'resorbtive state' as a potential repair mechanism. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2863